PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PORNOGRAFI YANG DILAKUKAN DENGAN TEKNOLOGI INFORMASI - Pristika Handayani (2008)
PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PORNOGRAFI YANG DILAKUKAN DENGAN TEKNOLOGI INFORMASI